Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4049/jimmunol.1102527
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Endothelial Nitric Oxide Synthase Expression by IL-17 in Human Vascular Endothelial Cells: Implications for Vascular Remodeling in Transplant Vasculopathy

Abstract: IL-17 is a signature cytokine of Th17 cells, a recently described subset of effector CD4 T cells implicated in the development of several pathologies. We have examined the role of IL-17 in regulating endothelial NO synthase (eNOS) expression in human vascular endothelial cells (ECs) because of the key role of eNOS in determining the pathological outcome of immune-mediated vascular diseases. In cultured ECs, IL-17 increased expression of eNOS, eNOS phosphorylation at Ser1177, and NO production. The induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
(48 reference statements)
1
15
0
1
Order By: Relevance
“…Our data showed that the immunoreactivity of IL-17 was located predominantly in the innermost medial layer of the pulmonary arterioles, so we investigated whether IL-17 affects the functions of PAECs. An MTT analysis showed that the maximal proliferation response by PAECs occurred with10 ng/mL IL-17 (figure 4A), which we chose for subsequent experiments as the stimulating concentration, as it was consistent with a previous study 14. Correspondingly, a BrdU incorporation assay showed that 10 ng/mL rhIL-17 increased the percentage of BrdU-stained PAECs (P4, S phase of the cell cycle), indicating IL-17-induced the proliferation of PAECs (figure 4B).…”
Section: Resultssupporting
confidence: 81%
“…Our data showed that the immunoreactivity of IL-17 was located predominantly in the innermost medial layer of the pulmonary arterioles, so we investigated whether IL-17 affects the functions of PAECs. An MTT analysis showed that the maximal proliferation response by PAECs occurred with10 ng/mL IL-17 (figure 4A), which we chose for subsequent experiments as the stimulating concentration, as it was consistent with a previous study 14. Correspondingly, a BrdU incorporation assay showed that 10 ng/mL rhIL-17 increased the percentage of BrdU-stained PAECs (P4, S phase of the cell cycle), indicating IL-17-induced the proliferation of PAECs (figure 4B).…”
Section: Resultssupporting
confidence: 81%
“…39 Interestingly, IL-17 binds to its receptor composed of IL-17RA and IL-17RC subtypes, leading to activation of the canonical ERK1/2, phosphoinositide 3-kinase-Akt, c-Jun N-terminal kinase, and p38 mitogen-activated protein kinase pathways. 40 We have shown that KCNK3 expression was reduced in patients with iPAH and hPAH and in MCT-PH rats. Interestingly, we have also previously demonstrated that PH induced by cyclophosphamide in rats is associated with a 70% reduction in KCNK3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of Cells-A549 cells were harvested by trypsinization, and 1 ϫ 10 6 cells were transfected with 6 g of wild type or 6 g of C118S Ras plasmid using an Amaxa nucleofector as per the manufacturer's instructions (Lonza) and as described previously (45). The wild-type (WT) and C118S Ras plasmids were kindly provided by Dr. Kenneth Tang (Cornell University).…”
Section: Methodsmentioning
confidence: 99%